HISTORY OF THE HAJJ DEVELOPMENT IN TURKEY: HISTORICAL AND CONTEMPORARY PERSPECTIVE - Bagaskara, Faishal Sultan (Jurnal Manajemen Dakwah, 2023)
The management of the Hajj pilgrimage in Turkey continues to evolve as the ruling government regime changes. During the Ottoman Turkish period, the Hajj was managed directly by the Sultanate. When the Republic of Turkey was established and gradually eliminated the religious aspect, the religious institution also transformed, followed by the Religious institution which was then managed by the State which upholds secularism. This article examines the development of Hajj in the Republic of Turkey from a historical and contemporary perspective by tracing the process of change in accordance with political conditions from the Ottoman Turkish period to the modern period. The finding of this research is that the dynamics of religious activities, especially Hajj, cannot be dissociated from the influence of political transformations that occurred throughout the Ottoman Turkish era, the Republic until the 21st century. The method used in this research is descriptive analytical which refers to the historical research method.